(untitled) (Revista de Crítica Literaria Latinoamericana, 2013)
This article proposes a postcolonial reading of some passages of the famous book by Pascale Casanova, The World Republic of Letters (2004). It makes visible French assumptions that sustain Casanova’s interpretation of Latin American modernity. Playing with the title of an old film by William Friedkin, the author names the narrative based on these assumptions, The French Connection. He analyzes three striking key moments in its development within the book of Casanova. Firstly, the moment of literary independence that would be obtained by Ruben Darío at the end of the 19th century; secondly, the moment of the liberating discovery of "authentic" Latin American identity that would occur in Paris during the avant-garde era, and lastly, the global recognition that would come in the 1960s with the literature of the Boom novels. The author argues for a change of perspective beyond the myth of French universalism which may allow us to understand France, its society, its peculiarities and characteristics within the context of the strategies, the logic and the beliefs that nourish its complex power relationship with Latin American culture.